Fracture Risk Assessment Tool (FRAX)® - Sieklucka, Ewa Monika; Ogurkowski, Karol; Stocka, Barbara; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2019)
For many years, there were no models for Polish population. Prospective studies showed that the use of British data model is reliable for the Polish patients, as supported by Przedlacki21,26,27 and others. Lately, a new version of the FRAX® method, including Polish data was introduced28,29. This triggered writing of the current paper, to continue farther studies of this population. Use of the described method to monitor treatment or to evaluate patients already treated, is pointless. Still, the method should be popularized, since only 10% of patients after an osteoporotic fracture are treated for the underlying condition3. The goal should be prevention of future fractures, return of independence in the activities of daily living and mobility.